Whole exome sequencing and DNA methylation analysis in a clinical amyotrophic lateral sclerosis cohort. Issue 4 (12th June 2017) - Garton, Fleur C.; Benyamin, Beben; Zhao, Qiongyi; Liu, Zhijun; Gratten, Jacob; Henders, Anjali K.; Zhang, Zong‐Hong; Edson, Janette; Furlong, Sarah; Morgan, Sarah; Heggie, Susan; Thorpe, Kathryn; et al.
Abstract: Background: Gene discovery has provided remarkable biological insights into amyotrophic lateral sclerosis (ALS). One challenge for clinical application of genetic testing is critical evaluation of the significance of reported variants. Methods: We use whole exome sequencing (WES) to develop a clinically relevant approach to identify a subset of ALS patients harboring likely pathogenic mutations. In parallel, we assess if DNA methylation can be used to screen for pathogenicity of novel variants since a methylation signature has been shown to associate with the pathogenic C9orf72 expansion, but has not been explored for other ALS mutations. Australian patients identified with ALS‐relevant variants were cross‐checked with population databases and case reports to critically assess whether they were "likely causal, " "uncertain significance, " or "unlikely causal." Results: Published ALS variants were identified in >10% of patients; however, in only 3% of patients (4/120) could these be confidently considered pathogenic (in SOD1 and TARDBP ). We found no evidence for a differential DNA methylation signature in these mutation carriers. Conclusions: The use of WES in a typical ALS clinic demonstrates a critical approach to variant assessment with the capability to combine cohorts to enhance the largely unknown genetic basis of ALS. Abstract : We use whole exome sequencing (WES) and methylation data to develop a critical, clinically relevant approach to identify a subset of ALS patients harboring likely pathogenic mutations. Published ALS variants were identified in >10% of patients; however, in only 3% of patients could these be confidently considered pathogenic (in SOD1 and TARDBP ). A differential DNA methylation signature was not identified in these mutation carriers, but remains to be explored for other causal variants in larger cohorts.